The solution of differential equation x y 3 ( 1 + cos x ) − y d x + x d y = 0 is

Solution of the equation x d y − y + x y 3 ( 1 + log x ) d x = 0 is

The solution of x + y d y / d x y − x d y / d x = x sin 2 x 2 + y 2 y 3 is given by

The solution of the differential equation x d y d x = y + x e y / x is

Solution of the differential equation d y d x = 2 x − y + 1 x + y + 2 is

The solution of differential equation x d y y 2 e x y + e x / y = y d x e x / y − y 2 e x y , is

The solution of differential equation 3 x 1 − x 2 y 2 d y d x + 2 x 2 − 1 y 3 = a x 3 is

Solution of the differential equation x + 2 y 3 d y d x = y is

If f ( 1 ) = 0 and d f d x > f ( x ) ∀ x ≥ 1 , then

x cos x d y d x + y ( x sin x + cos x ) = 1 then xy =

The solution of the differential equation sin x + cos x d y + cos x − sin x d x = 0 is

The solution of the differential equation d y d x = 2 x y − 3 y + 2 x − 3 is

The solution of the differential equation 1 − x 2 sin − 1 x d y + y d x = 0 is

If x 2 y d x − x 3 + y 3 d y = 0 , y 0 = 1 and y 3 log y = k x 3 then k =

If ϕ x = ∫ ϕ x − 2 d x and ϕ 1 = 0 then ϕ x =

Solve the differential equation 1 − x y + x 2 y 2 d x = x 2 d y

Solution of differential equation d y d x + x sin 2 y = sin y cos y is

General solution of x d y d x + y = y 2 x 3 cos x , is

The solution of 2 y cos y 2 d y d x − 2 x + 1 sin y 2 = ( x + 1 ) 3 is

The solution of d.E y 2 x 2 y + e x d x − e x + y 3 d y = 0 is

The solution of differential equation 2 y + x y 3 d x + x + x 2 y 2 d y = 0 is

Solution of differential equation d z d x + z x log z = z x 2 ( log z ) 2 is

The solution of sin x y ( y d x − x d y ) = x y 3 ( x d y + y d x ) is

The solution of sec 2 θ d θ + tan θ ( 1 − r tan θ ) d r = 0 is

Solution of differential equation d t d x = t d d x ( g ( x ) ) − t 2 g ( x ) is

The solution of differential equation x + y y 1 y − x y 1 = x 2 + 2 y 2 + y 4 x 2 is

If d y d x = x y + 2 x + 3 y + 6 then y ( − 1 ) − e 2 y ( − 3 ) =

Solution of differential equation x 2 1 x 2 + y 2 ( x d y + y d x ) + y 2 ( x d y − y d x ) = 0 is

The solution of the DE 2 x 3 y d y + 1 − y 2 x 2 y 2 + y 2 − 1 d x = 0 is

If x ⋅ ln x ⋅ d y d x + y = 2 ln x , y ( e ) = 2 then y e 2 =

If y − cos x ⋅ d y d x = y 2 ( 1 − sin x ) cos x , y ( 0 ) = 1 then y π 3

If d y d x = x y + y x y + x , then the solution of the differential equation is

The solution of the differential equation x d y − y d x = x 2 + y 2 d x is

The solution of the differential equation d y d x = x + y 2 x + 2 y − 2 is

The solution of y 5 x + y − x d y d x = 0 is

The solution of d y d x = x + y − 1 + x + y log x + y is given by

The solution of the differential equation x d x y = f x y f 1 x y d x is

A solution of the differential equation y x y − 1 d x + x y ln x d y = 0 , when y 2 = 1 is

x 2 y 3 + x y d y d x = 1 , y ( 1 ) = 0 , y = 2 when x =

An equation of the curve satisfying x d y – y d x = x 2 – y 2 d x and y ( 1 ) = 0 is

The solution of the differential equation d y d x = x y + x + y + 1 is

The solution of differential equation d y d x = 1 − y 2 y determines family of circles with

The general solution of the differential equation d y d x + sin x + y 2 = sin x − y 2 is

The solution of the differential equation x 4 + y 4 d x − x y 3 d y = 0 is

Solution of the differential equation x sin y x d y = y sin y x − x d x is

The solution of the differential equation y d y d x = x e x 2 + y 2 is

The solution of the differential equation, y d x + x + x 2 y d y = 0 is

The solution of the differential equation d y d x = 2 x y − 3 y + 2 x − 3 is

The solution of y 1 + x − 1 + sin y d x + x + log e x + x cos y d y = 0 is

Solution of the differential equation y − x d y d x = a y 2 + d y d x

The solution of the differential equation x d y d x + y = x 3 y 6 is

The solution of the differential equation d y = tan 2 x + y d x

The solution of the differential equation y d x + x d y x cos y x = x d y − y d x y sin y x is

The solution of y 2 x 2 y + e x d x − e x + y 3 d y = 0 , if y 0 = 1 is

The solution of the differential equation y 2 d y = x x d y − y d x e x / y is

The solution of differential equation 1 − x y + x 2 y 2 d x = x 2 d y is

The solution of the differential equation y 1 + 3 x 2 y e x 3 d x = x d y is

If x d y − y d x + x cos ( ln x ) d x = 0 , y ( 1 ) = 1 , then y ( e )

The solution of differential equation y d x − 1 + e − x y 2 d y = 0 is

Solution of x y 4 + y d x − x d y = 0 is

The solution of differential equation x d x − y d y x d y − y d x = 1 + x 2 − y 2 x 2 − y 2 is

The solution of d.E x 2 + y 2 + x d x − 2 x 2 + 2 y 2 − y d y = 0 is

The solution of e x y 2 − 1 y x y 2 d y + y 3 d x + { y d x − x d y } = 0 is

Solve x y 2 − e 1 x 3 d x − x 2 y d y = 0

The solution of differential equation d y d x = 1 − x ( y − x ) − x 3 ( y − x ) 3 is

The solution of the differential equation e x 2 + e y 2 y d y d x + e x 2 x y 2 − x = 0 is

If x 2 x 2 − 1 d y d x + x x 2 + 1 y = x 2 − 1 then y x − 1 x − ln x =

Integrating factor of x d y d x = 2 y + 2 x 4 + x 2

Solution of the differential equation 1 + y + x 2 y d x + x + x 3 d y = 0 is

The solution of d y d x + a y = e m x is (where a + m = 0 )

The solution of ( 6 x + 7 y − 4 ) d x + ( 7 x − 4 y + 3 ) d y = 0 is

The solution of the differential equation d y d x = x − 2 y + 1 2 x − 4 y is

If d y d x + y x = x 2 then 2 y ( 2 ) − y ( 1 ) =

If d y d x + y sec x = tan x then ( 2 + 1 ) y π 4 − y ( o ) =

If x d y = 2 y + 2 x 4 + x 2 d x , y ( 1 ) = 0 then y ( e ) =

The curve satisfy the differential equation 1 − x 2 y 1 + x y = a x are

If d y d x + x sin 2 y = x 3 cos 2 y , y ( 0 ) = 0 then tan y ( 1 ) =

If y = y ( x ) and 2 + sin x y + 1 dy dx = − cos x , y ( 0 ) = 1 then y ( π / 2 ) is

If dy dx = y + 3 > 0 and y ( 0 ) = 2 then y ( log 2 ) is

The solution of the DE cos x d y = y ( sin x − y ) d x , 0 < x < π 2 is

The solution of d y d x = x 2 + y 2 + 1 2 x y satisfying y ( 1 ) = 1 is given by

If x d y d x = x 2 + y − 2 , y ( 1 ) = 1 then y ( 2 ) is

The solution of the differential equation x 2 dy dx cos 1 x − ysin 1 x = − 1 When y − 1 as x ∞ is

Let yey(t) be a solution to the differential equation y 1 + 2 ty = t 2 then 16 lim t ∞ y is

If y = y ( x ) and it follows the relation 4 xe xy = y + 5 sin 2 x , then y 1 ( 0 ) is

The solution of the equation d y d x = x ( 2 log x + 1 ) siny+ycosy is

The general solution of the differential equation d y d x + sin ( x + y ) 2 = sin ( x − y ) 2 is

If y + x dy dx = x φ ( xy ) φ 1 ( xy ) then φ ( xy ) is

The solution of the D.E yy 1 = x y 2 x 2 + f y 2 x 2 f 1 y 2 x 2 is

The solution of D.E is x + y d y d x y − x d y d x = x cos 2 x 2 + y 2 y 3 is

The solution of the D . E x x 2 + 1 d y d x = y 1 − x 2 + x 3 log x is

The solution of the D.E [ x coty + log cos x ] d y + ( logsiny-ytanx ) d x = 0 is

The solution of the D.E 2 y + x y 3 d x + x + x 2 y 2 d y = 0 is

The solution of the D.E x + 2 y 3 d y d x = y is

The solution of the D.E 2 x 2 y dy dx = tan x 2 y 2 − 2 xy 2 , given that y ( 1 ) = π 2 is

The general solution of the differential equation y ( 1 − xy ) dx = x ( 1 + xy ) dy is

If x 3 d y d x = y 3 + y 2 y 2 − x 2 and y = 1 when x = 1 then y = 2 when x is

The general solution of the differential equation y 5 x 4 y + 1 dx + x + 2 y + 2 x 5 y dy = 0 i s

The general solution of d y d x = 2 y tan x + tan 2 x is

The degree of the differential equation d 2 y dx 2 2 + dy dx 2 = xsin d 2 y dx 2 is

The differential equation of all parabolas whose axes are parallel to the axis of ‘y’ is

The differential equation all conics whose centre lie at the origin is of order

The solution of the differential equation x 3 dy dx + 4 x 2 tany = e x secy satisfying y 1 =0 is

The solution of the differential equation x x 2 + y 2 d y = y x 2 + y 2 − 1 d x is

The general solution of the differential equation y x 2 y + e x dx − e x dy = 0 is

The solution of the differential y xy + 2 x 2 y 2 dx + x xy − x 2 y 2 dy = 0 is given by

The equation of the curve whose slope is y − 1 x 2 + x and which passes through the point (1,0) is

The solution of d y d x + 2 y t a n x = sin x , given that y = 0 , x = π / 3 is

The equation of the family of curves which intersect the hyperbola xy=2 orthogonally is

The solution of x log x d y d x + y = 2 log x is

The solution of d y d x = x − 2 y + 3 2 x − y + 5 is

The solution of the differential equation dy dx = sin ( x + y ) tan ( x + y ) − 1 is

The solution of ydx − xdy + 3 x 2 y 2 e x 3 dx = 0 is

The solution of y 3 cos x dx − x e 1 / y 2 dy = 0 is

The solution of d y d x + 3 x y = 1 x 2 , given that y = 2 , x = 1 is 2 x 3 y = x 3 + λ then λ is

The solution of cos y + ( x siny − 1 ) dy dx = 0 is xsecy = Ptany + c then ‘ P ′ is

The general solution of y ‘ + x y = 4 x is given by